Comparative contract law - Haley, John Owen, 1942- (International library of comparative law, 2017)
As cross-border transactions expand in our contemporary global economy, the significance of comparative contract law is evermore apparent. In addition the role of lawyers in transactional counselling as well as dispute resolution has become increasingly prominent. Appreciation of the principal similarities and differences between the two major subdivisions of Common Law - the United States and the British Commonwealth - and Civil Law - French versus German law - has thus become imperative. This research review endeavours to facilitate such appreciation and will prove an essential reference point for students, researchers and policymakers.